Minocycline blocks glial cell activation and ventilatory acclimatization to hypoxia - Stokes, Jennifer A.; Arbogast, Tara E.; Moya, Esteban A.; Fu, Zhenxing; Powell, Frank L. (Journal of neurophysiology, 2017)
Ventilatory acclimatization to hypoxia (VAH) is the time-dependent increase in ventilation, which persists upon return to normoxia and involves plasticity in both central nervous system respiratory centers and peripheral chemoreceptors. We investigated the role of glial cells in VAH in male Sprague-Dawley rats using minocycline, an antibiotic that inhibits microglia activation and has anti-inflammatory properties, and barometric pressure plethysmography to measure ventilation. Rats received either minocycline (45mg/kg ip daily) or saline beginning 1 day before and during 7 days of chronic hypoxia (CH, Pi O 2 = 70 Torr). Minocycline had no effect on normoxic control rats or the hypercapnic ventilatory response in CH rats, but minocycline significantly ( P < 0.001) decreased ventilation during acute hypoxia in CH rats. However, minocycline administration during only the last 3 days of CH did not reverse VAH. Microglia and astrocyte activation in the nucleus tractus solitarius was quantified from 30 min to 7 days of CH. Microglia showed an active morphology (shorter and fewer branches) after 1 h of hypoxia and returned to the control state (longer filaments and extensive branching) after 4 h of CH. Astrocytes increased glial fibrillary acidic protein antibody immunofluorescent intensity, indicating activation, at both 4 and 24 h of CH. Minocycline had no effect on glia in normoxia but significantly decreased microglia activation at 1 h of CH and astrocyte activation at 24 h of CH. These results support a role for glial cells, providing an early signal for the induction but not maintenance of neural plasticity underlying ventilatory acclimatization to hypoxia. NEW & NOTEWORTHY The signals for neural plasticity in medullary respiratory centers underlying ventilatory acclimatization to chronic hypoxia are unknown. We show that chronic hypoxia activates microglia and subsequently astrocytes. Minocycline, an antibiotic that blocks microglial activation and has anti-inflammatory properties, also blocks astrocyte activation in respiratory centers during chronic hypoxia and ventilatory acclimatization. However, minocycline cannot reverse ventilatory acclimatization after it is established. Hence, glial cells may provide signals that initiate but do not sustain ventilatory acclimatization.